The Conditions Optimization of Separation Screening and Degradation for Formaldehyde Degrading Bacteria In Soil - Ziyuan Li; Haiyun Li; Huixiang Zhang; Xiuli Wang; Liangmao Wei (Chemical Engineering Transactions, 2017)
In order to isolate five kinds of bacteria which can degrade the formaldehyde and optimize the degradation conditions, the paper has done the following works: the formaldehyde degrading bacteria were selected in Yanshan campus of Guilin University of Technology after enrichment culture, screening, re-screening and purification. The strain which had the best degradation ability was used for fermentation conditions optimization by single factor experiment. The optimum fermentation conditions of a strain formaldehyde degrading bacteria isolated on purpose are as follows: the inoculation amount is 0.20%, the temperature is 30°C, the initial pH value is 7.0, aldehyde addition is every 100ml medium with 0.020ml formaldehyde and speed is 140r/min. Conclusion: under certain fermentation conditions, the formaldehyde degrading bacteria has a certain ability of formaldehyde degradation.